Improved modelling of trains braking under low adhesion conditions. (2nd July 2020) - Alturbeh, Hamid; Lewis, Roger; Six, Klaus; Trummer, Gerald; Stow, Julian
ABSTRACT: Predicting the behaviour of trains when braking under low adhesion conditions presents considerable challenges. This paper describes an approach to the problem using a model of the full train braking system known as LABRADOR (Low Adhesion Braking Dynamic Optimization for Rolling Stock) and an improved method for representing the creep force–creepage behaviour when low adhesion is presently known as WILAC (Water Induced Low Adhesion Creep Force Model). The development of these models and their integration are summarized and a number of test cases are presented to demonstrate the improvements which can be gained from this approach. A number of suggestions are made for future enhancements with the aim of providing brake engineers and systems integrators with reliable simulation tools for optimizing train braking performance when low adhesion is present.